Barriers to digital marketing adoption at remote rural tourism destinations in Sarawak: an exploratory study - Cheuk, Sharon; Atang, Azuriaty; Lo, May Chiun; Ramayah, T. (American Scientific Publishers, 2017)
Rural tourism has been shown to benefit local communities from the economic perspective. Digital marketing allows marketing information to be transmitted directly to potential visitors without the need for an intermediary, in a low-cost but effective way. Rural tourism destinations in Sarawak now have an opportunity to benefit from the Sarawak state government’s initiative, the Digital Sarawak Centre of Excellence, in terms of digital content creation and website maintenance. However, the current level of adoption is zero to minimal in rural tourism destinations. This study examines the barriers towards digital marketing adoption from the perspective of rural tourism providers. Fieldwork was performed at two sites, Ba’kelalan and Long Lamai, in July 2016 and February 2017 respectively. In-depth interviews were conducted with a total of 19 respondents. The study revealed that tourism providers currently depended on word-of-mouth recommendations or direct contact for bookings, but were willing to adopt digital marketing with the assistance of knowledgeable parties. However, certain physical, logistical and social constraints may have a detrimental effect on the community’s readiness level to entertain tourists on a larger scale and may further impede the overall progress of digital marketing adoption, at both the individual and destination levels.